2022
DOI: 10.1161/circinterventions.122.012294
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Multiple Comparison of Transcatheter Aortic Valves: Insights From the Multicenter OBSERVANT II Study

Abstract: BACKGROUND: Head-to-head comparisons of devices for transcatheter aortic valve implantation (TAVI) are mostly limited to 2-arm studies so far. The aim of this study was to compare simultaneously outcomes of the most used, second- and third-generation transcatheter aortic valves in a real-world population. METHODS: A total of 2728 patients undergoing TAVI with different second- and third-generation devices, and enrolled in the multicenter, prospective OB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…They redemonstrated permanent pacemaker implantation (PPI), and new onset left bundle branch blocks were more prevalent with self-expandable valves (notably PPI was high among all groups, 16.0% versus 17.4% versus 9.6% versus 9.6% versus 18.2%) and intra-annular balloon-expandable SAPIEN 3 had lower rates of paravalvular leak (PVL) but higher residual transvalvular gradients. 1 This confirms prior investigation and may enable operators to provide patients reassuring data that any of the major TAVR platforms is equally safe, in terms of stroke, heart failure hospitalization, and death at 1 year.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…They redemonstrated permanent pacemaker implantation (PPI), and new onset left bundle branch blocks were more prevalent with self-expandable valves (notably PPI was high among all groups, 16.0% versus 17.4% versus 9.6% versus 9.6% versus 18.2%) and intra-annular balloon-expandable SAPIEN 3 had lower rates of paravalvular leak (PVL) but higher residual transvalvular gradients. 1 This confirms prior investigation and may enable operators to provide patients reassuring data that any of the major TAVR platforms is equally safe, in terms of stroke, heart failure hospitalization, and death at 1 year.…”
supporting
confidence: 81%
“…In this issue of Circulation: Cardiovascular Interventions , Costa et al present real-world findings from the OBSERVANT II study (Observational Study of Effectiveness of TAVI With New Generation Devices for Severe Aortic Stenosis Treatment), 1 head-to-head comparisons of market-dominant TAVR platforms from 2016 to 2018: Evolut R, Evolut PRO, SAPIEN 3, ACCURATE Neo, and Portico. In their intermediate-risk (EuroSCORE II of 5.1% [3.1–8.0]) older (83 years [79–86]) patient population, the predominant valve implanted was Evolut R (41.2% [n=1125]), and access was mostly transfemoral (91.4% [n=2493]).…”
mentioning
confidence: 99%
“…A study by Hase et al 25 of 1-year follow-up after TAVI showed that patients undergoing the Evolut R had a lower mean gradient and a higher index effective orifice area (EOA) compared with the Sapien 3, which is consistent with the finding of this study. Furthermore, Costa et al 26 presented a real-world population comparison of the Evolut R, Evolut PRO, SAPIEN 3, ACURATE neo, and Portico groups. This study demonstrated that patients treated with Sapien 3 had higher transprosthetic gradients.…”
Section: Valve Type Comparisonmentioning
confidence: 99%